Upaya Meningkatkan Fokus Belajar Siswa Kelas VII-A pada Materi Bilangan Bulat melalui Penerapan Ice Breaking ‘Tepuk Variasi’ di Awal Pembelajaran - Amilia Farah Dina; Arini Hidayati; Lifia Sulistiowati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to improve the learning focus of Grade VII-A students at SMP Islam Ar Rofi'iyyah on integer material through the application of the 'Varied Claps' ice breaking at the beginning of learning. The research uses Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of planning, action, observation, and reflection. The subjects were 28 students of Class VII-A. Data were collected through observation, interviews, and documentation. The results showed a significant increase in student learning focus. In the pre-cycle, the percentage of focused students was only 42.86%. After applying the 'Varied Claps' ice breaking in Cycle I, the percentage increased to 67.86%. In Cycle II, with improvements in the ice breaking application, the percentage reached 85.71%. This increase is supported by qualitative data showing students were more enthusiastic, ready to learn, and actively participated. The conclusion is that the application of 'Varied Claps' ice breaking is effective in increasing student learning focus on integer material.